2021
DOI: 10.1007/s11244-021-01419-y
|View full text |Cite
|
Sign up to set email alerts
|

An Inelastic Neutron Scattering Investigation of the Temporal Behaviour of the Hydrocarbonaceous Overlayer of a Prototype Fischer-Tropsch to Olefins Catalyst

Abstract: A dual sodium and sulfur promoted haematite, representative of a candidate Fischer-Tropsch to olefins (FTO) catalyst, is prepared and contrasted with the performance of an unpromoted hematite sample in the ambient pressure CO hydrogenation reaction at 623 K as a function of time-on-stream (0–24 h). In-situ post-reaction temperature-programmed oxidation measurements show the carbon evolutionary phase of the catalyst conditioning process to be retarded for the FTO catalyst. Ex-situ inelastic neutron scattering m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Running the same reaction at 1 bar results in only methane formation, so all the products are gaseous, but the catalyst is the same in both cases. This model reaction has been used for extensive studies of iron-based catalysts for both FTS [49][50][51][52][53] and FTO [54][55][56].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Running the same reaction at 1 bar results in only methane formation, so all the products are gaseous, but the catalyst is the same in both cases. This model reaction has been used for extensive studies of iron-based catalysts for both FTS [49][50][51][52][53] and FTO [54][55][56].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 99%
“…The INS studies reported in [48][49][50][51][52][53][54][55][56] all concern iron-based catalysts and there is clearly more that could be done, particularly regarding the effect of the additives that direct FTS to FTO. The cobalt-based systems have not been investigated by neutron scattering, apart from a study that aimed to characterise the states of adsorbed hydrogen on a range of cobalt catalysts [57].…”
Section: Fischer-tropsch Synthesismentioning
confidence: 99%